2022
DOI: 10.3390/ijerph19158923
|View full text |Cite
|
Sign up to set email alerts
|

Why Employees Experience Burnout: An Explanation of Illegitimate Tasks

Abstract: Among the many workplace stressors, a new type of stressor has been identified: illegitimate tasks. This newly identified type of stressor refers to work tasks that do not meet employee role expectations and constitute a violation of professional identity. To investigate illegitimate tasks’ mediating mechanisms and boundary conditions on job burnout, we examined a cross-level first-stage moderated mediation model with the collective climate as a moderator and psychological entitlement as a mediator. Grounded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 70 publications
5
14
0
Order By: Relevance
“…Second, the length of service/age ratio was a statistically significant predictor of burnout for all the subscales, indicating lower levels of burnout with a longer time invested in the organization. This effect has been observed in other studies, where increasing age reduces burnout levels ( Fila and Eatough, 2020 ; Ouyang et al, 2022 ; Werdecker and Esch, 2021 ). Third, although the type of organization was not a statistically significant predictor, the trend indicated that professionals working in public organizations were more likely to develop burnout.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Second, the length of service/age ratio was a statistically significant predictor of burnout for all the subscales, indicating lower levels of burnout with a longer time invested in the organization. This effect has been observed in other studies, where increasing age reduces burnout levels ( Fila and Eatough, 2020 ; Ouyang et al, 2022 ; Werdecker and Esch, 2021 ). Third, although the type of organization was not a statistically significant predictor, the trend indicated that professionals working in public organizations were more likely to develop burnout.…”
Section: Discussionsupporting
confidence: 84%
“…Correlation analysis showed similar patterns as reported in the literature. Illegitimate tasks were highly correlated to burnout subscales with higher correlation strength for the work-related burnout subscale, as described by other authors ( Kilponen et al, 2021 ; Ouyang et al, 2022 ; Werdecker and Esch, 2021 ). Finally, a univariate regression analysis in Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The concept illegitimate tasks has been studied in various settings and in relation to a variety of outcomes ( Ding and Kuvaas, 2022 ; Semmer,2019 ). For instance, it has been found to be associated with negative health and emotional effects, such as lower self-esteem ( Sonnentag and Lischetzke, 2018 ), poorer sleep ( Semmer et al., 2015 ), increased cortisol release ( Kottwitz et al., 2013 ), increased anger and frustration ( Eatough et al., 2016 ), higher incidence of musculoskeletal pain ( Kottwitz et al., 2021 ) and higher risk of burnout (e.g., Ouyang et al., 2022 ; Semmer et al., 2019 ). There is also research that focuses specifically on dimensions related to motivation, though not including RNs.…”
Section: Introductionmentioning
confidence: 99%